Patterns of retreatment with radiotherapy in a large academic centre. Issue 5 (9th May 2013) - Khor, Richard; Bressel, Mathias; Tai, Keen Hun; Ball, David; Duchesne, Gillian; Rose, William; Tedesco, Jo; Gill, Suki; Fitzpatrick, Claire; Foroudi, Farshad
Abstract Aims To characterise retreatment rates with radiotherapy at a large multifacility academic radiotherapy centre and assess the effect of distance on retreatment rate. Materials and Methods Electronic administrative records were reviewed for patients receiving radiotherapy between 1998 and 2010 at regional and metropolitan facilities. Course‐level data were reconstructed from electronic administrative databases. Intent of therapy, treatment dates and diagnosis were available for analysis. Retreatment characteristics were derived, including proportion of patients receiving retreatment, proportion of total radiotherapy prescriptions dedicated to retreatment and retreatment per treating facility. Travel distance for each patient to their treatment centre was estimated, and retreatment rates were reported as a function of increasing distance. Results A total of 48 200 patients were treated with 66 277 treatment courses during the study period. Retreatment courses constituted 25.2% of all courses prescribed. During the study period, 20.4% of all patients received at least one treatment course. Of these, the average number of retreatment courses prescribed was 1.84. Patients treated with radical intent had a retreatment rate of 13% compared with 45% for those treated initially with palliative intent. Retreatment rates in individual tumour sites ranged from 1.3 to 44.4%. The retreatment rate for those living less than 100 km from treatment facility was 24.8%, and 20.5% for those living more than 100 km from treatment centre (P < 0.001) Conclusion Retreatment accounted for over one quarter of radiotherapy courses, with the rate influenced by casemix and follow‐up duration. With increasing distance from treatment centre, a decrease in retreatment rate was observed.